Productivity Performance of the Service Sectors in European Union Countries - Wyszkowska‑Kuna, Joanna (Comparative Economic Research. Central and Eastern Europe, 2019)
Economic development has resulted in structural transformation towards economies based on services, which has raised some concerns about the limited opportunities for sustaining productivity growth. The aim of this paper is to examine total factor productivity (TFP) growth in the service sector in comparison with total industries and the manufacturing sector, as well as within the service sector. The study is based on the data from the EU‑KLEMS database (2017), and it covers the years 1995–2015. It refers to EU countries, making it possible to carry out a comparative analysis between countries, in particular between the ‘old’ and ‘new’ member states. The study demonstrates that productivity growth in services was significantly lower than in manufacturing, but compared with total industries, the disparity was not significant. Productivity growth was usually higher in the ‘new’ EU countries than in the ‘old’ ones, except for information and communications services, which, on the whole, were the main driving force behind the productivity growth in services.